Concealed antiaromaticity [version 1; peer review: 1 approved, 2 approved with reservations] - Florian Glöcklhofer (Open Research Europe)
The literature reports numerous molecules claimed to be antiaromatic because of a formal 4n π-electron system. However, this neglects the actual local aromaticity of the molecules, which often feature multiple subunits with [4n+2] π-electrons besides the formal 4n π-electron system. This has led to considerable criticism from those who believe that the term antiaromatic should not be used for any molecule with a formal 4n π-electron system but should be reserved for truly antiaromatic molecules. To reconcile the different viewpoints, the concept of concealed antiaromaticity is introduced here. Concealed antiaromaticity acknowledges that many molecules claimed to be antiaromatic are not truly antiaromatic, but they can exhibit behaviour under certain conditions that would normally be expected for antiaromatic molecules. Three types of concealed antiaromaticity are distinguished based on the conditions under which the molecules can behave like antiaromatic molecules: concealed antiaromaticity revealable in redox reactions (Type I-CA), upon photoexcitation (Type II-CA), and in intermolecular interactions (Type III-CA). The concept of concealed antiaromaticity will enable the rational design of molecules that show the desirable properties of antiaromatic molecules under the different conditions, with applications from organic electronics to photoresponsive materials, while avoiding the low stability of truly antiaromatic molecules.